2017
DOI: 10.1007/s00590-017-1918-8
|View full text |Cite
|
Sign up to set email alerts
|

Update review and clinical presentation in adult inferior dislocation of hip

Abstract: Inferior dislocation of the hip is a rare clinical entity, wherein closed reduction maneuver could be challenging, especially if the attending surgeon is not familiar with the specific anatomy associated with this injury. Due to the rarity of this type of injury, large case series are lacking in the literature; hence, case reports form the major source of our knowledge regarding the clinical presentation and management. An extensive literature search revealed a change in age group presenting with this specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There is no consensus on the management of hip dislocation after either open or closed reduction. Post-reduction immobilization using traction or cast and non-weight-bearing were recommended for the prevention of femoral head necrosis[ 5 , 26 ]. For old unreduced dislocation, traction is not only to reduce the risk of avascular necrosis, but also to ameliorate soft tissue contracture around the hip joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus on the management of hip dislocation after either open or closed reduction. Post-reduction immobilization using traction or cast and non-weight-bearing were recommended for the prevention of femoral head necrosis[ 5 , 26 ]. For old unreduced dislocation, traction is not only to reduce the risk of avascular necrosis, but also to ameliorate soft tissue contracture around the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…For old unreduced dislocation, traction is not only to reduce the risk of avascular necrosis, but also to ameliorate soft tissue contracture around the hip joint. The time of traction and non-weight-bearing following hip reduction is highly variable, ranging from 1 wk to 6 wk in traction and 2 wk to 12 wk in non-weight-bearing [ 4 , 5 , 7 , 8 , 11 , 14 , 18 , 20 , 22 , 26 ]. Although a few studies in recent years have shown that traction did not change the risk of avascular necrosis and prognosis[ 5 ], 6-wk skin traction and totally 8-wk non-weight-bearing were applied for our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation